Estudo da atividade anti-inflamatória de ricinus communis (Euphorbiacea) - Valderramas, Adriana Cristina (2006)
The interest for the research related to medicinal plants has been growing in the last years. Based on this fact, the medicinal plants have been considered source for new drugs obtained from natural products.The species of plant Ricinus communis, (Euphorbiaceae), has in its chemical composition the ricinoléic acid, an essential fatty acid derived from castor oil . This component has bactericidal action and its action mechanism is related to the citolitic function. It is also described that the castor oil presents a healing mechanism in the treatment of infected wounds, and also as an accomplice in antibacterial treatment.The castor oil plant presents biological and pharmacological action linked to the healing and against the microorganism action. Thereby our study evaluated the chronic and acute anti-inflammatory activity of the Ricinus communis in animal models. It was also studied the action mechanism of the R. communis in tests in vitro of anti-inflammatory activity. Finally tests of acute toxicity were carried out in mice.In the test of the mouse ear edema, R. communis (topical applied) showed a significant anti-inflammatory effect inhibiting the inflammation in 75% (p < 0.001). In the cotton pellet model, R. communis presented a chronic anti-inflammatory effect, inhibiting the inflammation in 62% (p<0.001). The oral administration of the R. communis inhibited 72% of the inflammation induced by formaline (p < 0.001). In experiments in vitro , the phospholipase A2 enzyme was also inhibited by the R. communis in a dose dependent manner.In the experiments of oral mucosal ulcers healing induced by NaOH 40%, the R communis showed a chronic anti-inflammatory effect, with a significant healing activity of around 60% (p<0.05).